DETERMINASI KINERJA KEUANGAN UMKM DI KABUPATEN BENGKALIS PADA MASA PANDEMI COVID 19: DETERMINATION OF THE FINANCIAL PERFORMANCE OF MSMEs IN BENGKALIS DISTRICT DURING THE COVID-19 PANDEMIC - Ayu Oktaviani; Alfiati Silfi; Fitri Humairoh (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2022)
The Covid 19 pandemic has had an impact on MSMEs. This study aims to determine and examine the effect of Equity Capital, Business Location, Length of Business, Number of Manpower and People's Business Credit on MSME financial performance. This research was conducted in Bengkalis Regency. The sample used in this study were 100 respondents of MSMEs registered at the Department of Industry, Trade, Cooperatives, and MSMEs in Bengkalis Regency with a random sampling technique. The type of data used in this research is quantitative data. Then the source of data used in this study is primary data. Data collected by using a questionnaire. The data analysis technique used is SPSS, 26The results of this study indicate that Own Capital, Business Location, Length of Business, Number of Manpower and People's Business Credit have a significant influence on MSME financial performance in Bengkalis Regency